A produção da talha joanina na capitania de Minas Gerais: retábulos, entalhadores e oficinas - Aziz José de Oliveira Pedrosa (2016)
The aim of this thesis is the study of luso-brazilian carving in the period called Joanine style according to the researcher Robert Smith in his book The carving in Portugal (1962). This study considered the woodcrafts produced in Minas Gerais between 1730-1760. This thesis is subsidized in documentary and bibliographic researches, formal and stylistic analysis of carving in the Joanine period of baroque in Minas Gerais. The methodolody made possible to analyse the Joanine style expressions in Portugal and its subsequent adaptation in Brazil, and then its settlement in Minas Gerais. This study analyses the altarpieces of some 18th century church in the cities Caeté, Ouro Preto, Mariana, São João-del Rei, Tiradentes, Ouro Branco, Santa Bárbara among others locations. It was also studied about the most important craftsman and ateliers in the period from 1730 to 1760, the influence of the books on architecture and ornament illustrations on woodcrafts in the mentionated period. As a result it was possible to make an overview of the Joanine period of Baroque carving in Minas Gerais.